Optical Coherence Tomography in Best Vitelliform Macular Dystrophy. Issue 2 (March 2017) - Battaglia Parodi, Maurizio; Iacono, Pierluigi; Romano, Francesco; Bolognesi, Gianluigi; Fasce, Francesco; Bandello, Francesco
Purpose: To analyze spectral-domain optical coherence tomography (SD-OCT)-specific findings in the different stages of vitelliform macular dystrophy (VMD). Methods: Thirty-seven patients were prospectively recruited. All the patients underwent a complete ophthalmologic examination, including best-corrected visual acuity (BCVA), biomicroscopy, and SD-OCT. The examined findings were vitelliform material, neurosensory detachment, intraretinal hyperreflective foci, and the status of external limiting membrane, ellipsoid zone, and retinal pigment epithelium. The primary outcome was the stratification of SD-OCT findings in each VMD stage. Secondary outcomes included the description of different characteristics related to intraretinal hyperreflective foci. Results: Outer retinal layers were preserved almost exclusively in stage 1 (range 70%-100%), whereas their disruption and absence were typical of stages 2 to 4 (83%-100%) and stage 5 (67%-83%), respectively. Vitelliform material was found always in stages 2 and 3, 89% of stage 4, and rarely in stage 5 (33%). Neurosensory detachment was to some extent representative of stages 3 and 4 (80% and 72%, respectively) when compared with the other stages (p<0.001). Hyperreflective foci (16% of all eyes) demonstrated a progressive increase across stages 2 to 4, with slightly reduced figure in stage 5. These foci were located in the outer nuclear and plexiform layers, showed different sizes, and were not associated with a visual acuity reduction (p = 0.64). Conclusions: A progressive deterioration of the outer retinal layers was noticeable in more advanced stages of VMD. The reduction of vitelliform material from stage 3 to 4 was paralleled by an increased evidence of neurosensory detachment. Although showing different size and location, hyperreflective foci did not correlate with worse BCVA.